Pengaruh Capital Adequacy Ratio (Car/Rasio Kecukupan Modal) dan Return on Assets (ROA / Rasio Pengembalian Atas Aset) Pada Stock Price (Harga Saham) PT. Bank Rakyat Indonesia (Persero) Tbk. - Yuaniko Paramitra, SE., MSM.; Febrianty Valentine (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
This study was conducted with the aim of testing and analyzing either partially or simultaneously the effect of CAR and ROA on the Stock Price. The technique used in this study is multiple linear regression analysis and using statistical test software, namely SPSS. In this study, the data source used was secondary data. The number of samples used as many as 40 data sampling in this study using the purposive sampling method. The results of hypothesis testing indicate that CAR partially has a positive and significant effect on stock prices, ROA partially has a positive and significant effect on stock prices and CAR and ROA simultaneously have a positive and significant effect on stock prices, with the results of the coefficient of determination test, the value of R Square is 0.176 which means that CAR and ROA have a simultaneous effect of about 17.6%.